Pengaruh Variasi Konsentrasi Sukrosa dan Gelatin terhadap Mutu Marshmallow Buah Kemang (Mangifera kemanga) - Widawati, Lina (Jurnal Teknologi Agro-Industri, 2024)
Kemang fruit (Mangifera kemanga) has a sour and slightly sweet taste and has micronutrient potential. To improve the quality of kemang fruit, it can be processed into marshmallow. The aim of this research is to characterize the physical, chemical and organoleptic properties and analyze the benefits of kemang fruit marshmallow. In this study there were two treatments, namely sucrose concentration (40% and 50%) and gelatin concentration (10%, 12%, 12%). The results of the overrun analysis of kemang fruit marshmallow ranged from 23.25% to 25.39%. The results of the texture analysis of the kemang fruit marshmallow were between 140.00 mm and 301.33 mm. The water content of kemang fruit marshmallow was highest in the 40% sucrose concentration and 10% gelatin treatment, namely 47.55%. The total sugar content of kemang fruit marshmallow was highest in the 50% sucrose concentration and 14% gelatin treatment, namely 1.23%. Vitamin C in kemang fruit marshmallow was highest in the treatment with a sucrose concentration of 50% and gelatin 14%, namely 22.23%. Based on organoleptic test analysis, treatment with a sucrose concentration of 40% and gelatin 14% gave the highest assessment, namely in terms of color 4.05 (like), taste 4.11 (like), flavour 3.75 (like) and texture 4.00 (like).